If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x*9=27
We simplify the equation to the form, which is simple to understand
3x*9=27
Simplifying:
+27x=27
We move all terms containing x to the left and all other terms to the right.
+27x=+27
We simplify left and right side of the equation.
+27x=+27
We divide both sides of the equation by 27 to get x.
x=1
| -13y(-6y+13)-3(16y+11)=39y(2y-10)-8 | | -15y(17y+4)+7=-7(-7y+9)+3y(-85y-4) | | -11(-5x-5)=18(-12x+4)-5x-16(-19x-4)-10 | | 6+3x-2(x+4)=20 | | -9(5y-4)-8+15(10y+11)=8-9(-11y-7) | | 11+9(8z+16)=-6z+5-19(4z-9)+11(5z-10) | | 4/(z+2)-1/(3z+6)=11/9 | | y^4+y^3+2y^2=0 | | 6x+2=5x+6 | | 2x-3/6+3x-2/4+5x+6/12=4 | | 75=3(10t-3)6t | | 2+5x=7+4x | | -x-4=-2x | | -18(13y+12)=-17+16(13y+8)-15(9y+17) | | 2.X-4=140 | | 2xX-4=140 | | 8(x+7)=-72 | | -13y-25y=16y-19 | | 3x+3-3=9 | | -15y=-23y+8-24y | | 3/4(x-2)=21 | | -12z+25z-23z=15z-16 | | v-1/v-4=7/4 | | 14y=-26+30y+29y-22y | | Graphy=3x-4 | | -8y=-12+18y+7y-13y | | 12/(x)-(5)/(4x) | | -4-6z=4z+56 | | 12/x-5/4x | | -x-3=-2x | | -14+28x+26x=16x-12+8x | | -14-28x+26x=16x-12+8x |